Somatostatin Receptor Imaging–Guided Pasireotide Therapy in Medullary Thyroid Cancer With Ectopic Adrenocorticotropin Production. (January 2015) - Verburg, Frederik A.; Anlauf, Martin; Mottaghy, Felix M.; Karges, Wolfram
<x xml:space="preserve">Abstract</x> Abstract A 51-year-old man with a history of metastatic medullary thyroid cancer (MTC) presented with high adrenocorticotropin (ACTH) and urinary free cortisol levels. The diagnosis of ectopic ACTH production, a rare MTC complication, was established in this patient. PET/CT using the somatostatin analogue DOTA-(Tyr3)-octreotate labeled with 68gallium (68Ga-DOTATATE) was performed, showing positive radionuclide uptake in multiple MTC metastases. After this therapy with the novel somatostatin analogue, pasireotide was initiated after which urinary free cortisol and ACTH levels decreased. The present case thus illustrates a potential theranostic use of 68Ga-DOTATATE PET/CT in MTC.